Bolt Tension Control with a Direct Tension Indicator - Struik, John H.A.; Oyeledun, Abayomi O; Fisher, John W. (Engineering Journal, 1973)
Achieving the minimum required bolt tension in a high strength bolted friction-type joint is a primary factor, since the slip resistance of the joint is dependent on the bolt tension. Current specifications require that high strength structural bolts be tightened to at least 70 percent of the minimum required tensile strength. For the past two decades installation has been primarily controlled by either turn-of-nut or calibrated wrench tightening. The turn-of-nut method depends upon strain control as contrasted to the torque control of the calibrated wrench method. Since the turn-of-nut method is primarily strain control, the effectiveness of the method depends on the starting point and accuracy of the rotational measurements. The variability of torque control is well known and was one of the reasons for the development of. the turn-of-nut method. Bolts tightened by the turn-of-nut method may have the outer face of the nut match-marked with the protruding bolt point before final tightening, so that an inspector can visually note the nut rotation. If an impact wrench is used for tightening, a slight peening of the bolt heads or nuts gives an additional indication that the bolt has been tightened. However, if the need for more inspection of bolt tension is necessary, one must use a calibrated inspection torque wrench with all its uncertainties.